Discovery and characterization of hevein-like peptides in functional food and medicinal plants - Tay, Stephanie Victoria Choo Gek (Nanyang Technological University, 2021)
Hevein-like peptides (HLPs) are a family of cysteine-rich, structurally compact, plant defense peptides. However, they remain underexplored and poorly understood. The objectives of my thesis consist of two parts. The first part focuses on the discovery of novel HLPs and to examine their structure, biosynthesis, distribution, occurrence and functions in selected plants. They include two functional grains, Chenopodium quinoa (quinoa), Avena sativa (oats), and a medicinal plant, Eleutherococcus trifoliatus (Three-leaved Eleutherococcus， 苦力心). From these plants, I discovered 13 novel HLPs: three 6C-chitin-binding HLPs, nine 8C-chitin-binding HLPs and a 8C-non-chitin-binding HLP. The second part focuses on data mining using bioinformatics to identify 1204 novel HLPs from 252 plant families. Together this study suggests that HLPs are one of the largest family of CRPs and provides insights into their sequence, molecular and functional diversity, potentially leading to development of novel peptidyl drugs, antimicrobial agents and pathogen-resistant transgenic crops.